Exchange rate regimes and macroeconomic instabilities in Sub−Saharan Africa - Yaya, Camara Seydou (International Review, 2016)
This article addresses macroeconomic instabilities according to exchange rateregimes in Sub-Saharan Africa (SSA). Based on International Monetary Fund’s exchangerate regimes de facto classification, the global sample, SSA, is first divided into twosubsamples, which are countries within CFA franc zone (ZCFA) and those outside CFAfranc zone (HZCFA), and then into four categories, which are the Western Economic andMonetary Union (WAEMU), the Central African Economic and Monetary Community, thecountries CFA franc zone with fix exchange rate regimes(HZCFA-FIX), and the countriesoutside CFA franc zone with flexible exchange rate regimes(HZCFA-FLEX). By applyingadvanced statistical and econometric methods upon internal and external macroeconomicequilibrium conditions, we show that the inflation, the GDP (or the output) and the realexchange rate (RER) are very volatile in SSA. However, we found out that they are morevolatile in the group HZCFA comparatively to the group ZCFA. We also found out that theyare higher in the group HZCFA-FIX than the group HZCFA-FLEX. Moreover, we foundout that a high instability of the inflation is combined with those of the output and the RER.